2017
DOI: 10.1002/jcb.25942
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Enhances Self‐Renewal of Mouse Embryonic Stem Cells

Abstract: Resveratrol (RSV) has been shown to affect the differentiation of several types of stem cells, while the detailed mechanism is elusive. Here, we aim to investigate the function of RSV in self-renewal of mouse embryonic stem cells (ESCs) and the related mechanisms. In contrast with its reported roles, we found unexpectedly that differentiated ESCs or iPSCs treated by RSV would not show further differentiation, but regained a naïve pluripotency state with higher expressions of core transcriptional factors and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…There is little data uncovering resveratrol-dependent signaling pathways that regulate mESC pluripotency 16,33 . Here we show the mechanism of resveratrol action on pluripotency based on the mTORC1 pathway inhibition and autophagy activation via AMPK/Ulk1 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…There is little data uncovering resveratrol-dependent signaling pathways that regulate mESC pluripotency 16,33 . Here we show the mechanism of resveratrol action on pluripotency based on the mTORC1 pathway inhibition and autophagy activation via AMPK/Ulk1 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol induces neuronal differentiation in murine neuroblastoma cells (Namsi et al, 2018) and differentiation of monocytes to macrophages (Vasamsetti et al, 2016). Recent reports show that resveratrol increases self-renewal and maintains the pluripotency of human and mouse embryonic stem cells (Li et al, 2017;Safaeinejad et al, 2017). Intragastric administration or resveratrol causes activation of cardiac stem cells, an increase of capillary density, and reduction of apoptosis of cardiomyocytes, which may be beneficial in myocardial regeneration after acute myocardial infarction (Ling et al, 2017).…”
Section: Anti-ageing Activitymentioning
confidence: 99%
“…From the perspective of telomeres, Res could attenuate telomere dysfunction through by activating Werner syndrome ATP-dependent helicase (WRN helicase), which contributes to telomere maintenance [48]. Furthermore, it has been reported that Res provides protective effects to damaged stem cells, such as embryonic stem cells (ESCs) [49], embryonic neural stem cells [50], and SSCs [17], by maintaining genomic stability and accelerating recovery from DSBs (double-strand breaks) [16]. However, there has been little research about whether Res has protective functions in a chemotherapy-induced ovarian aging model and whether Res could exert protective effects on female germline stem cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%